Enhancing Organizational Resilience Through the Synergy of Capital Resources and Dynamic Capabilities - AHACHMI, Mustapha; LAHFIDI, Abdelhaq (Revue Internationale des Sciences de Gestion, 2025)
In a context marked by multiple crises, pandemics, climate disruption, and geopolitical instability, strengthening organizational resilience is a strategic imperative, particularly for small and medium-sized enterprises (SMEs) in the tourism sector. Drawing on dynamic capabilities theory (DCT) and social capital theory, this study analyzes how intangible resources, financial, social, and technological capital, contribute to organizational resilience, both directly and through the mediating role of dynamic capabilities. Based on a survey of 206 Moroccan hotel SMEs and structural equation modeling using PLS-SEM, the results show that financial and social capital have a significant effect on dynamic capabilities and resilience. Technological capital, although having a non-significant direct effect, influences resilience indirectly via dynamic capabilities. The study highlights the central role of dynamic capabilities as a mechanism for converting intangible resources into adaptive capabilities. These results enrich the theoretical understanding of resilience as a dynamic capability and offer concrete implications for managers and public decision-makers.